La guerra justa y el fin de la historieta (Un manifiesto neomoderno) - Carlos Escudé (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
– If all cultures are morally equivalent, then all individuals are not essentially endowed with the same human rights, because some cultures award some men more rights than are allotted to other men and women. If, on the other hand, all men and women are endowed with the same human rights, then all cultures are not morally equivalent, because cultures that acknowledge that all men are created equal are ethically superior to those that do not. These two statements are mutually contradictory and cannot both be true. Moreover, there is a natural conflict between them, leading to inevitable intra and inter-civilizational clashes. Relativism will confront evolutionism and hierarchical theocracy will confront secularized republicanism. This essay takes sides and argues that cultural superiority can be asserted on two different levels: moral and epistemological. A culture that acknowledges a set of universal human rights is superior to one that does not, even if it often deviates from these very norms. A culture capable of delving into nature increasing life expectancy through scientific discovery is superior to one that cannot. Furthermore, waging war to defend a superior culture is a moral imperative.
Keywords: 330